The effect of alpha-lipoic acid supplementation on anthropometric indices and food intake in patients who experienced stroke: A randomized, double-blind, placebo-controlled clinical trial - Mohammadi, Vida (J Res Med Sci, 2017)
BACKGROUND: Stroke as a devastating condition is a major cause of death worldwide. It is accountable for long-term disability with high personal and social cost in adults. Alpha-lipoic acid (ALA) is an eight-carbon, sulfur-containing compound with antioxidant properties which reduces body weight, changes other anthropometric indices, and regulates food intake by suppressing appetite and increasing metabolism This study was designed to evaluate the possible effects of ALA supplementation on anthropometric indices and dietary intake in patients with stroke. MATERIALS AND METHODS: In this randomized, double-blind, placebo-controlled clinical trial, 67 patients with stroke were randomly allocated to two groups (taking a 600 mg ALA supplement or placebo daily for 12 weeks). Weight, waist circumference, energy, carbohydrate, protein, and fat intake were measured, and body mass index (BMI) was calculated before and after intervention. Dietary intake and statistical analyses were carried out using Nutritionist IV and SPSS (version 16; SPSS Inc., Chicago, IL, USA) software, respectively. RESULTS: Primary features were similar in the intervention and placebo groups (P > 0.05). Waist circumference (P < 0.001), energy, carbohydrate, protein, and fat intake (P < 0.001) decreased significantly, after the intervention period, in ALA group compared with placebo. While no significant change was observed in weight (P = 0.26) and BMI (P = 0.56) in ALA supplementation group compared with placebo. CONCLUSION: Results of this trial indicated that 12-week supplementation with 600 mg ALA can decrease waist circumference and food intake (energy, carbohydrate, protein, and fat) in patients with stroke.